2003
DOI: 10.1038/sj.bmt.1704223
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow vs extramedullary relapse of acute leukemia after allogeneic hematopoietic cell transplantation: risk factors and clinical course

Abstract: Summary:A total of 118 consecutive adult patients with acute leukemia (78 AML, 36 ALL, and four acute mixed lineage leukemia) underwent allogeneic hematopoietic cell transplantation (HCT) after conditioning with BuCy (n ¼ 113) or a nonmyeloablative regimen of busulfanfludarabine (n ¼ 5). After a median follow-up of 35.8 months (range, 6.4-91.0), 34 patients experienced at least one episode of leukemia relapse. Of 34 initial episodes, 14 (41%) occurred in extramedullary sites, with (n ¼ 8) or without (n ¼ 6) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 32 publications
9
102
5
Order By: Relevance
“…2,37,41,42 Although it should be interpreted cautiously, considering the limited number of patients in our study, our finding, that all the initial relapses after DLI occurred only at extramedullary sites, suggests that these isolated extramedullary relapses might occur more frequently after DLI than after BMT. Although the reason this uneven GVL effect between marrow and extramedullary sites tends to be stronger in the post-DLI than in the post-BMT setting remains unknown, it is possible that the patients enrolled in our study may represent a selected group.…”
Section: Figurementioning
confidence: 57%
“…2,37,41,42 Although it should be interpreted cautiously, considering the limited number of patients in our study, our finding, that all the initial relapses after DLI occurred only at extramedullary sites, suggests that these isolated extramedullary relapses might occur more frequently after DLI than after BMT. Although the reason this uneven GVL effect between marrow and extramedullary sites tends to be stronger in the post-DLI than in the post-BMT setting remains unknown, it is possible that the patients enrolled in our study may represent a selected group.…”
Section: Figurementioning
confidence: 57%
“…This is not only reported for MM, but also for acute leukaemias. 15,16 These EM relapses are believed to indicate transformation of the disease, associated with a more aggressive behaviour, therapy resistance and short survival. However, reports regarding this subject in MM are lacking data on the efficacy of the relapse treatment or are case reports.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the relapse rate after such transplantation remains high, especially for the high-risk disease states, the relapse rate can reach up to 23-50%. [3][4][5] Different modified conditioning regimens, including intensive chemotherapeutic blocks, using promising new agents before transplantation, have been explored to achieve and sustain MRD negativity. Some nonrandomized studies on the use of an intensified conditioning have reported better disease control for high-risk patients, but higher rates of toxicity and TRM have also been reported.…”
Section: Introductionmentioning
confidence: 99%